A Method of Pricing for a Socialist Economy. - Gordon, Myron J. (The Accounting Review, 1970)
The article presents the set of rules for determining transfer prices that can serve as a feasible and efficient instrument for the decentralized administration of a socialist economy. The problems of bureaucracy in the management of a socialist economy are if anything more acute than the problems of a large firm in a capitalist economy. The classical solution to the decentralized administration of a socialist economy was stated most clearly by O. Lange. Lange proposed a socialist economy in which firm managers exploited their monopoly power to influence prices might be more or less efficient than a centralized economy. The article examines the so-called accounting and economic theories on the relation between cost and production and establishes the role each plays in the administration of a firm. It presents a model of cost behavior which results is the foundation for the transfer price system. It finally describes how cost, price and production are determined under the system and examines the consequences of the system for the allocation and utilization of resources.